Welfare State - Silva, Filipe Carreira da (2018)
Silva, F. C. da (2017). Welfare State. In William Outhwaite, Stephen Turner (Eds.), The SAGE Handbook of Political Sociology, 2v, pp. 944-957. London: Sage